1983
DOI: 10.1007/bf00257338
|View full text |Cite
|
Sign up to set email alerts
|

Glibenclamide-associated hypoglycaemia: A report on 57 cases

Abstract: In the largest series of patients with glibenclamide-associated hypoglycaemia reported so far, 51 cases reported to the Swedish Adverse Drug Reactions Advisory Committee and six additional cases are reviewed and related to sales and prescription data of glibenclamide. Median age of the patients with hypoglycaemia was 75 years and 21% were 85 years or above. For comparison, the median age of a random sample (1 in 288 of all patients prescribed glibenclamide) was 70 years and only 5% were 85 years or older. In e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
103
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(110 citation statements)
references
References 21 publications
6
103
1
Order By: Relevance
“…However, in our case the patient had no past medication history of such kind. The presentation of our patient is consistent with the results of a report on 57 cases by Asplund and colleagues in which a fatal outcome was observed even with small doses of glibenclamide (2.5-5 mg/day) [Asplund et al 1983]. The contributing factors, including impaired renal function, poor intake and diarrhoea were present in the current case.…”
Section: Discussionsupporting
confidence: 92%
“…However, in our case the patient had no past medication history of such kind. The presentation of our patient is consistent with the results of a report on 57 cases by Asplund and colleagues in which a fatal outcome was observed even with small doses of glibenclamide (2.5-5 mg/day) [Asplund et al 1983]. The contributing factors, including impaired renal function, poor intake and diarrhoea were present in the current case.…”
Section: Discussionsupporting
confidence: 92%
“…The UK Prospective Diabetes Study (UKPDS) showed that improving glycemic control reduced longterm microvascular complications (2). However, intensive therapy increases the risk for severe hypoglycemia, which is associated with mortality and morbidity (3,4).…”
mentioning
confidence: 99%
“…Glyburide (called glibenclamide in Europe), the most widely used sulfonylurea (7), has a relatively long terminal half-life in chronic dosing compared with other sulfonylureas, owing to its high affinity for the ␤-cell sulfonylurea receptor and the accumulation of active metabolites that are excreted through the kidney (7). Several observational studies have reported increased rates of hypoglycemia with the use of glyburide compared with other sulfonylureas (3,4). A systematic review of randomized controlled trials (RCTs) evaluating the risk for hypoglycemia associated with the use of glyburide has not, to our knowledge, been previously conducted.…”
mentioning
confidence: 99%
“…10 A high mean age also characterised a series of glibenclamide-treated patients with Type 2 diabetes in whom severe hypoglycaemia was reported to the Swedish Adverse Drug Reactions Advisory Committee. 14 In this study, 24 of the 57 patients reviewed had protracted hypoglycaemia, and 10 patients died. In some cases, fatal outcomes occurred when doses were as low as 2.5 ± 5 mgaday.…”
Section: Drug-induced Hypoglycaemia In Type 2 Diabetes: How Common?mentioning
confidence: 78%